The Conformation of the Mature Dimeric Human Immunodeficiency Virus Type 1 RNA Genome Requires Packaging of Pol Protein - Shehu-Xhilaga, M. (American Society for Microbiology, 2002)
The packaging of a mature dimeric RNA genome is an essential step in human immunodeficiency virus type 1 (HIV-1) replication. We have previously shown that overexpression of a protease (PR)-inactive HIV-1 Gag-Pro-Pol precursor protein generates noninfectious virions that contain mainly monomeric RNA (M. Shehu-Xhilaga, S. M. Crowe, and J. Mak, J. Virol. 75:1834-1841, 2001). To further define the contribution of HIV-1 Gag and Gag-Pro-Pol to RNA maturation, we analyzed virion RNA dimers derived from Gag particles in the absence of Gag-Pro-Pol. Compared to wild-type (WT) dimeric RNAs, these RNA dimers have altered mobility and low stability under electrophoresis conditions, suggesting that the HIV-1 Gag precursor protein alone is not sufficient to stabilize the dimeric virion RNA structure. The inclusion of an active viral PR, without reverse transcriptase (RT) and integrase (IN), rescued the stability of the virion RNA dimers in the Gag particles but did not restore the mobility of the RNAs, suggesting that RT and IN are also required for virion RNA dimer maturation. Thin-section electron microscopy showed that viral particles deficient in RT and IN contain empty cone-shaped cores. The abnormal core structure indicates a requirement for Gag-Pro-Pol packaging during core maturation. Supplementing viral particles with either RT or IN via Vpr-RT or Vpr-IN alone did not correct the conformation of the dimer RNAs, whereas expression of both RT and IN in trans as a Vpr-RT-IN fusion restored RNA dimer conformation to that of the WT virus and also restored the electron-dense, cone-shaped virion core characteristic of WT virus. Our data suggest a role for RT-IN in RNA dimer conformation and the formation of the electron-dense viral core.